You Can Help Every Provider Have a Better Understanding of Functional Behavior Assessment! A Review of the Website: Basic FBA to BSP. (December 2017) - Shultz, Gwendolyn Joy; Havens, Nathan; Gurney, Beth Newberry; Burt, Jon
Managing problematic classroom behavior is a challenge for many teachers, regardless of population. The website, www.basicfba.com, designed by researchers at Portland State University, offers teachers and practitioners a wealth of materials to assist them in conducting and maintaining a functional behavior assessment and behavior support plan. Tools are also provided to allow participants to graph and analyze data. This article gives an overview of the resources available and how they may be used.